Analisis Resepsi Fanbase "Kelelawar" terhadap Transformasi Identitas (Rebranding) Band .Feast - Maulana, Isa; Nurliah (Jurnalika : Jurnal Ilmu Komunikasi, 2025)
This study aims to analyze the reception of the "Kelewar" fanbase towards the identity transformation or rebranding carried out by the band .Feast. This transformation includes changes in aesthetics, ideology, and musical direction that are quite significant, and have caused various responses from fans. Using a qualitative approach with the reception analysis method according to Stuart Hall, this study classifies audience responses into three categories: dominant-hegemonic, negotiation, and opposition. Data were collected through in-depth interviews with active fanbase members, as well as documentation of their interactions on social media. The results of the analysis show that most fans are in a dominant-hegemonic position by fully supporting the changes, the rest are able to accept some elements of the changes while questioning the new values ​​brought by the band. There are also fans who reject it, because they feel that the forum for political critics with a commercial style has been lost. This study shows that the fanbase is not only passive, but active in reinterpreting the new symbols and identities offered by the artist. These findings strengthen the importance of the audience perspective in the study of popular culture, especially in the context of Indonesian independent music.